Multispan bridges with distributed deck and pier mass and pier‐flexure‐deck‐torsion coupling under transverse excitation—Analytical solution, parametric studies, design implications. (14th August 2021) - Fardis, Michael N.
Abstract: An "exact" analytical dynamic model is developed for symmetric bridges with two to five spans under transverse earthquake. It considers the mass as distributed along the deck and the piers and accounts for coupling of deck torsion with pier bending in vertical planes normal to the deck's axis. The characteristic equation is formulated in terms of (up to) seven dimensionless parameters which fully define a bridge and is solved numerically. Commercial software is used to validate the solution. Parametric studies of 225 bridge layouts produce response results of key importance for seismic design. Specific and general conclusions are drawn for conceptual design of multispan bridges for transverse earthquake.